0230 Sleep and Interrogation: Does Losing Sleep Impact Criminal History Disclosure?. (27th May 2020) - Krizan, Z; Miller, A; Meissner, C
Abstract: Introduction: Despite centuries of using sleep deprivation during interrogation, there is virtually no scientific evidence on how sleep shapes behavior in interrogation settings. Moreover, investigative interviews are often conducted at night, or with fatigued subjects. To evaluate the impact of sleeplessness on subjects' behavior during investigative interviews, an experimental study examined the impact of moderate sleep restriction on information disclosure and behavioral reactions during interviews about past illegal acts. Methods: Healthy participants (N=120) were recruited from the university community and randomly assigned to either maintain or curb their sleep (up to 4 hours a night) across two days. Back in the laboratory individuals privately indicated whether they committed various illegal acts. Participants were interviewed while video-recorded about the most severe act they acknowledged. After the initial disclosure, participants listened to a 'model' statement, an unrelated example of a person's detailed event account designed to encourage additional disclosure, after which they again provided information about their offense. Key variables were the severity of the illegal behavior reported and the amount of information provided before and after the model statement (blindly coded from transcripts for quantity and quality). Results: Sleep-restricted participants slept on average 4.5 hours less (confirmed via actigraphy), reported no differences in perceived treatment by the interviewer, and tended to report less severe offenses. Critically, sleep-restricted participants provided almost 20% less information during their initial disclosure (d = .53, p =.01). After the model statement, however, disclosure was generally higher and similar across conditions (d = .15, p = .35). Sleep-restricted individuals also reported less overall motivation to recall information (d=.27, p = .01). Conclusion: Results suggest that even moderate sleep loss can inhibit criminal disclosure during interviews, and that reduced motivation could play a role. Also, the use of the model statement could compensate for this effect. Support: N/A